A novel phantom with dia- and paramagnetic substructure for quantitative susceptibility mapping and relaxometry - Emmerich, Julian; Bachert, Peter; Ladd, Mark E.; Straub, Sina (Physica medica, 2021)
Purpose: A phantom is presented in this study that allows for an experimental evaluation of QSM reconstruction algorithms. The phantom contains susceptibility producing particles with dia- and paramagnetic properties embedded in an MRI visible medium and is suitable to assess the performance of algorithms that attempt to separate isotropic dia- and paramagnetic susceptibility at the sub-voxel level. Methods: The phantom was built from calcium carbonate (diamagnetic) and tungsten carbide particles (paramagnetic) embedded in gelatin and surrounded by agarose gel. Different mass fractions and mixing ratios of both susceptibility sources were used. Gradient echo data were acquired at 1.5 T, 3 T and 7 T. Susceptibility maps were calculated using the MEDI toolbox and relaxation rates Delta R*2 were determined using exponential fitting. Results: Relaxation rates as well as susceptibility values generally coincide with the theoretical values for particles fulfilling the assumptions of the the static dephasing regime with stronger deviations for relaxation rates at higher field strength and for high susceptibility values. MRI raw data are available for free academic use as supplementary material. Conclusions: In this study, a susceptibility phantom is presented that might find its application in the development and quantitative validation of current and future QSM reconstruction algorithms which aim to separate the influence of isotropic dia- and paramagnetic substructure in quantitative susceptibility mapping.
Gesehen am 11.10.2021